Comparison of Cervical Lymph Nodes Dissection for Excisional Biopsy “Simple Dissection Technique vs. Improvised Loop Traction Technique” - Tahir Iqbal Mirza, Aima Tahir, Ansar Latif, Asif Alam Gul, Fasiha Yousaf, Hira Malik, Hira Shami, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare improvised loop traction dissection with simple dissection technique for lymph node excisional biopsy of cervical region Study design: Cohort study. Place: Combined Military Hospital Rawalpindi, Abbottabad, Multan & Peshawar. Duration: September 2013 – January 2022. Methodology: cervical region Lymph nodes with intact architecture more than 1 centimeter were considered for this study while lymph nodes of the cervical region with distorted architecture and size <1cm were not included in this study. Among 530 patients, two dissection techniques (simple and improvised loop) were adopted. The lymph nodes to be removed were detected with palpation or through ultrasound and imaging such as computed tomography (CT). An open biopsy surgical procedure with or without modification was adopted. In the first group-I (n=206), Lymph node dissection was continued with the conventional technique, and in the group (n=324) lymph node was inserted with a silk suture for traction as the loop is adopted. The post-procedural assessment was for the difficulty level of dissection was done. Results: Among 530 Patients (Male=76.03%: Female=23.96%), the mean age in years of the patient was simple dissection technique n=206(range=20-69 mean 39) and loop techniques n=324(mean 41 and range 21-66). On average, 19.30 minutes for loop improvised and structural preservation was 69.75% (226), while rupture with the simple technique was observed in about 18(8.7%). The dissection time was less among patients with improvised loop technique and architectural preservation. Conclusions: Inserting silk suture as a double loop reduces duration and facilitates dissection in preserving architecture of lymph node sample Keywords: improvised loop technique, griping& holding, preserved architecture